Зміни артеріального тиску та частоти серцевих скорочень, пов’язані з метеофакторами, у студентів. - Сопронюк, Євгенія; Козачук, Наталія; Поручинський, Андрій; Sopronyuk, Yevheniya; Kozachuk, Nataliya; Poruchynsky, Andriy (Східноєвропейський національний університет імені Лесі Українки, 2014)
Досліджено динаміку артеріального тиску та частоти серцевих скорочень у досліджуваних відповідно до зміни метеорологічних ситуацій. Визначено рівні метеочутливості здорових осіб віком 18–20 років за допомо¬гою тесту-опитувальника «Метеочутливість». Експериментально доведено наявність статистично достовірних кореляційних зв’язків між основними параметрами погоди та показниками серцево-судинної системи в осіб із високим та середнім рівнем метеочутливості та відcутність таких зв’язків у осіб із низьким рівнем метео¬чутливості. Найбільше кореляційних зв’язків виявлено між показниками серцево-судинної системи та атмо¬сферним тиском і температурою повітря. During the experiment the dynamics of blood pressure and heart rate in people aged 18−20 years have been investigated. The main purpose of the study is to determine the basic levels of meteosensitivity, to identify the main features of the dynamics of arterial pressure and heart rate associated with major weather factors within the students with different levels of meteosensitivity. The basic levels of human meteosensitivi¬ty have been determined by the results of the test-questionnaire «Мeteosensitivity» and indexes of the cardiovascular system such as: blood pressure and heart rate. According to the results all the individuals were divided in three groups: with low, average and high level meteosensitivity. The study of the dynamics of functional state main indicators person cardiovascular system with different meteosensitivity level, during the change of meteorological situations, has shown the link between the actual and theoretically calculated meteosensitivity. As a result, this study shows the close correlations between the major weather factors and indicators of cardiovascular system in persons meteosensitive and the absence of such dependencies in non-meteosensitive persons. The highest correlations has been found between the indicators of the cardiovascular system and the atmospheric pressure, air temperature.
Changes in Blood Pressure and Heart Rate, Related to Weather Factors, of Students
Keywords: рівень метеочутливості; артеріальний тиск; частота серцевих скорочень; метеорологічні параметри погоди; meteosensitivity level; blood pressure; heart rate; meteorological factors